2020
DOI: 10.1080/17461391.2020.1746835
|View full text |Cite
|
Sign up to set email alerts
|

Water‐based exercises in postmenopausal women: Vertical ground reaction force and oxygen uptake responses

Abstract: The purpose of the present study was to analyse vertical ground reaction force (Fz) and oxygen uptake (VO 2 ) responses in six different water-based exercises performed at different cadences by postmenopausal women. Twelve postmenopausal women (57.3 ± 2.6 years, 158.1 ± 6.9 cm, 69.1 ± 10.9 kg) voluntarily took part in the study. Participants completed six sessions corresponding to maximal tests for each water-based exercise. Then, two sessions were performed for the experimental protocols, which comprised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
2
5
0
1
Order By: Relevance
“…This magnitude is in accordance with previous studies, which observed a 69 to 71% reduction in the apparent weight in eutrophic young adults immersed at the same level [11,12,24]. On the other hand, recent studies have shown even greater reductions of 75 to 81% in adult women with obesity [13], as well as in postmenopausal [30] and older adult women [31]. Differences in the aging process and body composition (muscle mass, fat mass, and bone density) could explain such differences in the magnitude of reduction between the aforementioned studies [32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This magnitude is in accordance with previous studies, which observed a 69 to 71% reduction in the apparent weight in eutrophic young adults immersed at the same level [11,12,24]. On the other hand, recent studies have shown even greater reductions of 75 to 81% in adult women with obesity [13], as well as in postmenopausal [30] and older adult women [31]. Differences in the aging process and body composition (muscle mass, fat mass, and bone density) could explain such differences in the magnitude of reduction between the aforementioned studies [32].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effect of cadence on the performance of the stationary running exercise, an increase in Fz peak was observed in the aquatic environment from 80 to 100 b min −1 , while no difference was found between 60 b min −1 and the other cadences (mean values ranging between 0.8-1.0 BW). These findings partially agree with previous studies that showed an increased Fz peak as submaximal cadence increased for different water-based stationary exercises [11,13,19,24,30,34]. This increase in Fz peak is likely related to the fact that as cadence increases, individuals need to apply a greater propulsive force to adequately overcome water resistance and promote the vertical propulsion of their bodies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Water-based aerobic programs, on the other hand, have been shown as an important tool for minimizing such losses, improving cardiorespiratory, neuromuscular, and functional outcomes, as well as quality of life, in older individuals [7,21]. These exercises are also traditionally indicated to the older population because they provide a lower impact on lower limb joints [22] and cardiovascular overload [23] when compared to the land environment.…”
Section: Introductionmentioning
confidence: 99%
“…Additional physical properties of water, such as hydrostatic pressure and water's thermal conditions also promote important physiological effects in the human body [10,11], leading to benefits in hemodynamic, neuroendocrine, and metabolic parameters. Moreover, buoyancy promotes biomechanical alterations, such as a low ground reaction force during water-based exercises performance [12]. Collectively, these characteristics favor adherence of older individuals to this type of exercise, whose environment appears to be safe for those individuals who usually present cardiovascular and musculoskeletal disorders, highly prevalent in the elderly [13,14].…”
Section: Introductionmentioning
confidence: 99%